Control of mitochondrial dynamics and apoptotic pathways by peroxisomes - Jiang, Chenxing; Okazaki, Tomohiko (Frontiers in Cell and Developmental Biology, 2022)
Peroxisomes are organelles containing different enzymes that catalyze various metabolic pathways such as β-oxidation of very long-chain fatty acids and synthesis of plasmalogens. Peroxisome biogenesis is controlled by a family of proteins called peroxins, which are required for peroxisomal membrane formation, matrix protein transport, and division. Mutations of peroxins cause metabolic disorders called peroxisomal biogenesis disorders, among which Zellweger syndrome (ZS) is the most severe. Although patients with ZS exhibit severe pathology in multiple organs such as the liver, kidney, brain, muscle, and bone, the pathogenesis remains largely unknown. Recent findings indicate that peroxisomes regulate intrinsic apoptotic pathways and upstream fission-fusion processes, disruption of which causes multiple organ dysfunctions reminiscent of ZS. In this review, we summarize recent findings about peroxisome-mediated regulation of mitochondrial morphology and its possible relationship with the pathogenesis of ZS.